The Development of Mathematics Exercises Entitled, “Integer System” for Grade 7 Students - พวงสมบัติ, กนกกร; แสงพรหม, นฤมล; เสนารัตน์, เบญจมาภรณ์; เสนารัตน์, สมประสงค์ (Journal of Roi Et Rajabhat University, 2017)
The purpose of this research was to develop the mathematics exercises entitled, “Integer System” for grade 7 students. This research and development process was divided into 3 steps. The first step was construction of research instruments including; learning plans, mathematics exercises, an achievement test and a satisfaction questionnaire. The second step was the trial of research instruments with grade 7 students at Watkrokpradoo School, Buriram Primary Educational Service Area 1, in the academic year of 2014 and 2015. The third step was to assess an effectiveness index and efficiency indices of the mathematics exercises. Moreover, this step was also to analyze student satisfaction toward the mathematics exercises. The purposive sampling was utilized to recruit 9 grade 7 students for collecting the data at Watkrokpradoo School, Buriram Primary Educational Service Area 1, in the academic year of 2016. Results of the study revealed that the mathematics exercises were evaluated content validity at the highest level. The efficiency indices of the mathematics exercises (E1/E2) were 80.00/78.52 with an effectiveness index of 0.69. An analysis of student satisfaction toward the mathematics exercises showed that students were satisfied at the highest level.